PERBEDAAN PENGARUH METODE LATIHAN PLYOMETRIC DEPTH JUMP DAN HURDLE HOPPING TERHADAP PENINGKATAN POWER OTOT TUNGKAI PADA PESILAT REMAJA PUTRI PERGURUAN TAPAK SUCI PUTERA MUHAMMADIYAH SIMO BOYOLALI TAHUN 2018 - Sudarmanto, Eko (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
Based on the problems that have been formulated in this_studyotheoaimoisoto determineothe differencesoin the effect of Hurdle hopping and Depth Jump training on leg muscle power on Adolescent Female Female Student of Tapak Suci College Putera Muhammadiyah Simo Boyolali in 2018 and which exercises have better influence between Hurdle hopping trainingand Depth Jump on increasing leg muscle strength in the Young Women College of Tapak Suci, Putera Muhammadiyah Simo Boyolali in 2018. The research method used was experimental. Basedoonothe resultsoofotheoresearch, theofollowingoconclusionso can be obtained: There are differences in influence between Depth Jump training and the Hurdle Hopping exercise on the increase in Leg Muscle Power in Adolescent Female Female Fighters in the Tapak Suci College of Putera Muhammadiyah Simo Boyolali in 2014, withotocount =5.3508> totable =02.093. Depth Jump training has a better effect than the Hurdle Hopping exercise in mening said the Power of Leg Muscle in Young Women Pesilat in the Tapak Suci College of Putera Muhammadiyah Simo Boyolali in 2014, with an increase in Depth Jump training = 6.239%> Hurdle Hopping training = 4.278%. In this study, it turned out that Depth Jump training and Hurdle Hopping training both increased power Leg muscles with a significant increase. Fromothisostudy it0can beoseenothatoinogroups that use Depth Jumps training or inogroups that use Hurdle Hopping exercises both have been shown to increase leg muscle power. Fromothis studyoit canobe seen thatoin groups using Depth Jumps and group exercises. those using Hurdle Hopping training were both proven to increase leg muscle power. In this study, it turned out that Depth Jump training and Hurdle Hopping exercises were both able to increaseleg muscle power with a significant increase.